The effects of music therapy in patients with high‐dose chemotherapy and stem cell support: a randomized pilot study. Issue 3 (5th May 2016) - Tuinmann, Gert; Preissler, Pia; Böhmer, Hauke; Suling, Anna; Bokemeyer, Carsten
Abstract: Objective: Patients with high dose chemotherapy (HDC) with autologous stem cell transplantation (ASCT) are highly distressed. Psycho‐oncological support might be beneficial but is not routinely provided. Our aim was to investigate whether music therapy (MT) in addition to standard supportive treatment had any effect on quality of life, depression, anxiety, side effects of therapy, medication, and immunological changes during and within three months after HDC plus ASCT. Methods: Patients (n = 66) with HDC plus ASCT were randomly assigned to either MT (Intervention Group = IG) or standard supportive treatment (Control Group = CG). Quality of life was measured by EORTC QLQ‐C30. Depression and anxiety were measured by the HADS‐D before transplantation, during and after the inpatient stay. In addition, adverse events (AE), medication, and immunological parameters were observed. Results: There was no improvement of global quality of life for patients receiving additional MT, but their perception of pain significantly changed ( p  = 0.027). Patients were neither depressed nor anxious on admission, therefore no improvements were found. IG patients had less 3–4° toxicities (e.g., mucositis). Aprepitant for antiemetic therapy was administered significantly more often in the CG ( p  = 0.040). The IgA decline and T4 count was less in IG, T8, and NK count decreased most in IG. These findings failed significance. Conclusions: MT may improve pain perception in patients receiving HDC plus ASCT. Additionally positive effects on toxicities, use of antiemetic medication, and immunological changes were observed. As some of these findings failed significance, studies with larger sample sizes are needed. Copyright © 2016 John Wiley & Sons, Ltd.